THE MEANING OF VERBAL AND NONVERBAL SIGN IN CIGARETTE ADVERTISEMENTS - Ni Ketut Tila Ningsih; Ida Ayu Putri Gita Ardiantari (Universitas Aki, 2022)
Abstract This study entitled “The Meaning Of Verbal And Non Verbal Sign In Cigarette Advertisements